2021
DOI: 10.3390/cancers13153833
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of HIF-1α in the Detection, Signaling, and Repair of DNA Double-Strand Breaks after Photon and Carbon-Ion Irradiation

Abstract: Hypoxia-Inducible Factor 1α (HIF-1α), which promotes cancer cell survival, is the main regulator of oxygen homeostasis. Hypoxia combined with photon and carbon ion irradiation (C-ions) stabilizes HIF-1α. Silencing HIF-1α under hypoxia leads to substantial radiosensitization of Head-and-Neck Squamous Cell Carcinoma (HNSCC) cells after both photons and C-ions. Thus, this study aimed to clarify a potential involvement of HIF-1α in the detection, signaling, and repair of DNA Double-Strand-Breaks (DSBs) in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…[70,71] Hypoxia combined with IR stabilizes HIF-1α to inhibit the proliferation of tumor cells. [72] It is one of the reasons radiotherapy can be the most important therapeutic strategy for cancer treatment. However, IR cannot reduce the expression of HIF-1α and hypoxia is the leading cause of radiation resistance.…”
Section: Mechanism Of Avpt@hp@m For Rt Sensitizationmentioning
confidence: 99%
“…[70,71] Hypoxia combined with IR stabilizes HIF-1α to inhibit the proliferation of tumor cells. [72] It is one of the reasons radiotherapy can be the most important therapeutic strategy for cancer treatment. However, IR cannot reduce the expression of HIF-1α and hypoxia is the leading cause of radiation resistance.…”
Section: Mechanism Of Avpt@hp@m For Rt Sensitizationmentioning
confidence: 99%
“…Furthermore, supporting the lack of oxygen effect after C-ions, the same rejoining kinetics of DSBs were reported in oxic and hypoxic conditions after exposure. This is in favour of the same DSBs produced in both conditions but with modification of the contributions of the DNA repair mechanisms over time [ 55 , 56 ]. However, compared with photons, the repair time was longer after C-ions with more unrepaired damage, and whatever the oxygen concentration, these results support the ‘bomber’ effect of C-ions.…”
Section: Bomber Effects On Cancer Cellsmentioning
confidence: 99%
“…The authors indicated a possible link to the chromosomal instability status of cells and the possible absence of p53 and CHK2 activation (phosphorylation) but did not check effects on mitochondria. Interestingly, Wozny et al, showed that under hypoxia, silencing of HIF-1α that is translocating to the nucleus significantly radiosensitizes HNSCC and cancer stem cell subpopulations to photons and C-ion exposures because of decreased DSB detection by the ATM protein and decreased DSB repair by HR and NHEJ [ 288 ].…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%